2018
DOI: 10.1111/jch.13398
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma homocysteine and hypertension: Results from a cross‐sectional and longitudinal analysis in Beijing’s adult population from 2012 to 2017

Abstract: D141100000114003). All funding sources were independent and had no influence on the study design, the collection, analysis, and interpretation of our data, the writing of this report, or the decision to submit the article for publication. Plasma homocysteine (Hcy) levels are associated with elevated blood pressure.However, the causal association between Hcy levels and the risk of hypertension remains ambiguous. Taking the study design effect into consideration, this study aimed to investigate this issue throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
(59 reference statements)
0
11
0
1
Order By: Relevance
“…In 2017, a meta-analysis incorporating 15 studies worldwide also showed the positive causal relationship might be confounded by several factors ( 26 ). However, in 2018 Tao et al ( 8 ) described the gender-specific causal relationship based on a sample of 3,913 participants from a longitudinal cohort in Chinese population. Other studies from China also demonstrated positive relationship between Hcy level and hypertension ( 27 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, a meta-analysis incorporating 15 studies worldwide also showed the positive causal relationship might be confounded by several factors ( 26 ). However, in 2018 Tao et al ( 8 ) described the gender-specific causal relationship based on a sample of 3,913 participants from a longitudinal cohort in Chinese population. Other studies from China also demonstrated positive relationship between Hcy level and hypertension ( 27 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship could be greatly influenced by multiple factors such as race, gender, age, and nutritional supplementation ( 7 ). Recently, a large longitudinal study done by Tao et al ( 8 ) proved that serum Hcy level predicts hypertension. With a high prevalence of hypertension ( 9 ) and HHcy ( 7 ), Hcy might play a more important role in Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with high cholesterol levels, the administration of folic acid reduced the risk of stroke by 30% [67]. In recent years several large meta-analyses have been published, all of which stated that folic acid therapy and possibly with the addition of other B vitamins reduces the risk of stroke by 10%-15% [56,68,69]. A meta-analysis by Wanga et al assessed the efficacy of folic acid supplementation among patients with hypertension and hyperhomocysteinemia (homocysteine >10 µmol/l) [56].…”
Section: Administration Of Folic Acid In the Preventions Of Strokesmentioning
confidence: 99%
“…К "сосудистым" ФР МАГ относят и избыточную прокоагулянтную активность крови, нередко ассоциированную с НВ. Показано, в частности, что при повышенном АД сосудисто-тромбоцитарное звено гемостаза характеризуется усилением спонтанной и индуцированной агрегационной способности тромбоцитов, возрастанием активности фактора Виллебранда, что было особенно заметным на фоне увеличенной концентрации в крови гомоцистеина [37]. У больных МАГ средние значения последнего индикатора обычно ниже, чем при стабильной АГ, а показатели гемостаза характеризуются увеличением концентрации в крови фибриногена, тромбомодулина, ингибитора активатора плазминогена, активатора тканевого плазминогена.…”
Section: факторы риска и патофизиологические детерминанты магunclassified